Characteristics of Participants Enrolled onto a Randomized Controlled Trial of Palliative Care for Patients on Phase I Studies - Ferrell, Betty R. (J Palliat Med, 2017)
Introduction: Advanced cancer patients participating in phase 1 clinical trials experience considerable symptom burden. Palliative care (PC) may benefit these individuals by providing supportive care during clinical research participation. This study investigates integration of a PC intervention among phase 1 trial participants with advanced cancer. Methods and Materials: This study is a multisite randomized clinical trial testing a concurrent PC intervention among phase 1 trial participants. Baseline demographic and clinical characteristics and descriptive baseline assessment findings were examined for all participants to date. Self-report assessments included quality of life (QOL) using the Functional Assessment of Cancer Therapy-General, spirituality using the Functional Assessment of Chronic Illness Therapy-Spirituality, and overall distress using the Distress Thermometer. Clinical trial retention and healthcare utilization were assessed through chart audit at study completion. Results: The study has enrolled 178 participants to date. The average age is 60.3 years, the majority was Caucasian (57.9%), and participants had an average of 1.7 comorbidities. Overall QOL was 77.6 (±15.1). Responses were most favorable for social/family well-being (22.6 ± 4.6), lowest for emotional well-being (14.9 ± 5.1), and average overall distress was 3.6 (±2.7). Healthcare utilization at study completion (n = 134) identified low rates of supportive care referrals, with approximately half of participants referred to social work (50.8%), and fewer referred for pain (43%), resource centers (44%), and physical therapy (18%). Conclusion: Phase 1 clinical trial participants experience unmet QOL needs at baseline and levels of distress that merit clinical intervention. Although this study is in progress, initial findings support the potential benefits of PC among this population.